The grand design - Hawking, Stephen W. 1942-2018; Mlodinow, Leonard 1954- (Transworld Publishers, 2011)
Along with Caltech physicist Mlodinow (The Drunkard's Walk), University of Cambridge cosmologist Hawking (A Brief History of Time) deftly mixes cutting-edge physics to answer three key questions-- Why is there something rather than nothing? Why do we exist? Why this particular set of laws and not some other?-- and explains that scientists are approaching what is called "M-theory," a collection of overlapping theories (including string theory) that fill in many (but not all) the blank spots in quantum physics. This collection is known as the "Grand Unified Field Theories."
1. publ. in Great Britain in 2010 by Bantam Press
Keywords: Große Vereinheitlichung; Kosmologie; Einführung